2011
DOI: 10.1111/j.1439-0418.2011.01669.x
|View full text |Cite
|
Sign up to set email alerts
|

Male diet and age influence to inhibit female remating in Ceratitis capitata (Diptera: Tephritidae)

Abstract: This study evaluated the influence of age and adult nutritional status of Ceratitis capitata males on their ability to inhibit female remating. Their roles and that of copula duration on the amount of sperm transferred to female spermathecae were also analysed. After emergence, adults were kept in separate groups according to their diets (either high protein – 6.5 g of brewer’s yeast, or low protein – 3.5 g of brewer’s yeast) and their age at the time of use in experiments (4, 8, 12, 16 and 20 days old). The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 62 publications
1
26
0
1
Order By: Relevance
“…The lack of any correlation between copulation time and reproductive success in terms of the quantities of sperm transferred to the female was noted by Costa et al. (). Similarly, the differences in copulation times between the Peruvian and A .…”
Section: Discussionmentioning
confidence: 90%
“…The lack of any correlation between copulation time and reproductive success in terms of the quantities of sperm transferred to the female was noted by Costa et al. (). Similarly, the differences in copulation times between the Peruvian and A .…”
Section: Discussionmentioning
confidence: 90%
“…Similarly, Shelly et al (2007) found that middle-age males (5 or 10 d-old) are more effective in inhibiting female remating, compared to younger males (3-4 d-old). However, in another study on this same species, female remating was not influenced by male age (from 4 to 20 days-old) (Costa et al 2012). Likewise, in the Queensland fruit fly Bactrocera tryoni, male age did not affect their ability to inhibit female remating (Pérez-Staples et al 2008).…”
Section: Introductionmentioning
confidence: 93%
“…Specially, it can affect copulation duration (Koref-Santibanez 2001;Pérez-Staples et al 2008, mating success (Zuk 1988;Jones 2000;Jones and Elgar 2004;Fricke and Maklakov 2007;Pérez-Staples et al 2010;Papanastasiou et al 2011) and sperm traits (Taylor et al 2001;Pérez-Staples et al 2008;Papanastasiou et al 2011;Costa et al 2012;Decanini et al 2013;Santhosh and Krishna 2013). Females may prefer to mate with young males as they have less deleterious mutations in the germline and are more fertile Price 1995, 1999;Beck and Powell 2000;Beck and Promislow 2007).…”
Section: Introductionmentioning
confidence: 96%
“…Similarly, previous studies of T. angusticollis have only found subtle, context‐dependent effects of adult diet on male reproduction (Adler et al ., ; Macartney et al ., ). Protein is a key nutrient for male reproduction in other species (Droney, ; Baker et al ., ; Costa et al ., ), and it is therefore surprising that it has little influence on male reproduction in T. angusticollis . Male and female neriid flies require different quantities of developmental nutrients for optimal reproductive investment (Bonduriansky et al ., ), and this appears to equally apply to adult nutrient requirements.…”
Section: Discussionmentioning
confidence: 97%